2010
DOI: 10.1186/1743-8977-7-36
|View full text |Cite
|
Sign up to set email alerts
|

ISDD: A computational model of particle sedimentation, diffusion and target cell dosimetry for in vitro toxicity studies

Abstract: BackgroundThe difficulty of directly measuring cellular dose is a significant obstacle to application of target tissue dosimetry for nanoparticle and microparticle toxicity assessment, particularly for in vitro systems. As a consequence, the target tissue paradigm for dosimetry and hazard assessment of nanoparticles has largely been ignored in favor of using metrics of exposure (e.g. μg particle/mL culture medium, particle surface area/mL, particle number/mL). We have developed a computational model of solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
526
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(537 citation statements)
references
References 48 publications
10
526
1
Order By: Relevance
“…We hypothesize that this alteration to AuNP dosimetry is due to the increased particle stability and observed alteration to the protein corona. As smaller agglomerates allow for increased diffusion and NP transport, a greater fraction of AuNPs will reach the HaCaT surface (Cho et al 2011;Hinderliter et al 2010); thus increasing the deposition efficiency. This theory is further supported by the dynamic results, which introduced a new mode of NP transport and interfered in deposition.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this alteration to AuNP dosimetry is due to the increased particle stability and observed alteration to the protein corona. As smaller agglomerates allow for increased diffusion and NP transport, a greater fraction of AuNPs will reach the HaCaT surface (Cho et al 2011;Hinderliter et al 2010); thus increasing the deposition efficiency. This theory is further supported by the dynamic results, which introduced a new mode of NP transport and interfered in deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the concept of dose is more complex and dynamic for NP as it is for chemicals. To address this issue Teeguarden et al developed the concept of particokinetics to model the NP behaviour in dispersion based on its likelihood to diffuse, sediment and agglomerate in dispersion 116,131 . Since both diffusion and sedimentation are influenced by agglomeration, the latter is expected to have a major impact on the NP uptake and toxicity 169 .…”
Section: The Effect Of Particle Agglomeration and Sedimentationmentioning
confidence: 99%
“…The size and electro density of the AgNPs shows degradation, which appeared to be more severe in the lysosomes when comparing (N) versus (O). Zhu et al, 2013), others report it the other way around (Cho et al, 2011;Hinderliter et al, 2010), and also maximal uptake in a privileged size gap was reported (Chithrani et al, 2006;Varela et al, 2012). Higher uptake of larger NPs could be explained by sedimentation of the larger NPs onto the cells (Hinderliter et al, 2010), leading to increased cellular uptake (Cho et al, 2011).…”
Section: Cellular Uptakementioning
confidence: 99%